Potential of Trichoderma to improve probiotic performance in Vannamei shrimp cultivation - Sutarman; Prasetyo Dony; Hudi Lukman; Nurbaya Syarifa R.; Sriyono; Mulyadi (E3S Web of Conferences)
The purpose of this study was to determine the effect of microbe consortium on the physical characteristics of pools water and the growth of vannamei shrimp. The experiment was arranged in a Completely Randomized Design consisting of five types of microbe consortium treatments including Trichoderma, Lactobacillus, probiotic bacteria, Trichoderma-Lactobacillus, and Trichoderma-probiotic bacteria with a population density of 0.5x104 CFU.mL-1 for fungi and 104 CFU.mL-1 for bacteria. A total of 5,000 shrimp seeds were planted in each of the 15 circular pools with a volume of 12.56 m3. The parameters observed were pH, temperature, salinity, dissolved oxygen, water brightness, as well as Average Daily Growth (ADG), and Feed Conversion Rate (FCR). The data were analyzed through ANOVA followed by a 5% LSD test, and correlation analysis was also conducted. The results showed that Trichoderma either alone or in combination with the probiotic bacteria and Lactobacillus spp., increased the pH, temperature, salinity, dissolved oxygen, and water brightness as well as shrimp’s daily growth and feed utilization efficiency. ADG value has a positive correlation with the average increase in pH and water clarity. Meanwhile, FCR correlated with an elevation in ADG and pH, as well as a decrease in water brightness.